Orientation Use of Houses in Rural - Urban (A Case Study in the Eastern District of Kartasura, Sukoharjo 2001) - Choirul Amin; Dilahur Dilahur; Muhammad Musiyam (Forum Geografi, 2000)
Kartasura, seen formspace point of view, has special position because it is located in the corridor intersection between Semarang – Surakarta – Yogyakarta. Which becomes three central developing cities in central part of Java. This study is carried out in border town area in east part of Kartasura, which consist of four village – Pabelan, Gonilan, Gumpang, and Makamhaji. That are growing fast due to the effect of urban characteristic from Surakarta. The orientation phenomena of the use of house (OPR), the urban population that led to the commercial use is an interesting fact dealing with the influence of urban activities in those areas. The goal of this study is to know the kindsand the spread of the space of OPR population in east part of Kartasura and the factors, which is studied, is the houses in the research areas and the respondents are the owner of the houses. The sampling uses systematic proportional random sampling. The location of house sample (UMS, UNS, Islamic Boarding Shcool of Assalam), health services (RSIS and RSO), and commercial services (ALFA, UMS stores). All of them are located in Pabelan and Makamhaji. While industrial center consist of PT Tyfountex and small industries around it in Gumpang. Every central activities is divided into two cluster based on the relative distance from central activities (far and near), so as a whole there are four clusters which made up of two clusters in service center and the other in industrial center. Sample at every cluster is taken proportional about 2,5% based on homogenity consideration, whether the selecction of house sampling is taken randomly. The numbers of samples as a whole 175 respondents. The collected data are prensented in the form of frequency and cross table. Qualitative data analysis uses logical thought, deductive induccctive, analogy and comparison, while quantitative data analysis is done using frequency table analysis and cross table. The use of both analysis is sadapted with the data and goal of the study. The result of this  study shows that 1) OPR population in east part of Kartasura consist of three kinds, commercial OPR, non commercial, and combination. While the spreading space of the kind of OPR follows the concept of distance decay principle – the nearer relative distance of the house to the center of activities, the more commercial orientation the use of the house is. 2) External factor, which influence OPR, is the developing urban activities such industry, commerce, education, and health instrument. While the internal factor which influence to OPR is the size of land ownership.